PROSPECTS FOR THE TYPES OF FABRICS OBTAINED FROM TWISTED YARN (E Conference Zone, 2022)
The Ministry of Investment and Foreign Trade of the Republic of Uzbekistan together with the Ministry of Foreign Affairs, the Association of Textile Industry of Uzbekistan organizes international exhibitions of textile and fashion industry in Uzbekistan at least once a year, including textile events in the world calendar. Agreements with the European Union, Turkey, Korea, China and other countries will include the reduction of customs duties on national textile products and the simplification of regulatory measures.